THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS ON EMPLOYEE PERFORMANCE IN PT MATAHARI DEPARTMENT STORE BANDA ACEH - Eva Susanti; Nasrullah Nasrullah (University Muhammadiyah Aceh, 2020)
The purpose of this study was to examine the Accounting Information System on Employee Performance at PT. Matahari Depertment Store Banda Aceh. This research is a research using survey method with associative descriptive approach. This research was conducted from November 2018 to completion. The object in this study is the Accounting Information System on Employee Performance at PT. Matahari Depertment Store Banda Aceh The sample of this research is 39 respondents. Research data were collected through questionnaires, and documentation studies. The research data were analyzed using a simple linear regression model and processed using SPSS (Statistical Product and Service Solutions) version 22 assistance, the t test (partial) was intended to partially determine the effect of the independent variables on the dependent variable at the 95% confidence level (α = 0.05). The results showed that the Accounting Information System affects the Performance of Employees at PT. Matahari Depertment Store Banda Aceh. Accounting Information Systems have a strong relationship to Employee Performance at PT. Matahari Depertment Store Banda Aceh